HUBUNGAN ANTARA PENGETAHUAN DAN HYGIENE MAKANAN DENGAN KEJADIAN TYPHUS ABDOMINALIS - Rimbawati, Yazika; Wulandari, Yupika (JURNAL KESEHATAN TERAPAN, 2021)
Background: Typhus is common throughout the world and its distribution does not depend on the climate, but is more common in developing countries in the tropics (Juwono, 2010). Objective: To determine the relationship between knowledge and food hygiene with the incidence of abdominal typhus. Methods: This type of research is quantitative using a cross sectional study design with a sampling technique using accidental sampling obtained a sample of 82 respondents. Results: There was a relationship between knowledge p value = 0.021, food hygiene p value = 0.010 with the incidence of abdominal typhus. Suggestion: As a guideline or example for future researchers and can be used as information related to further research with different variables. Keywords: Knowledge, Food Hygiene, Stomach Tyhpoid